2021
DOI: 10.1177/15533506211014848
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role on the Use of Platelet-Rich Plasma Products in the Management of Urogynaecological Disorders

Abstract: Background: The regenerative efficacy of platelet-derived products has been recently investigated in the treatment of pelvic floor disorders (PFDs). We aimed to synthesize the current evidence of platelet-rich plasma (PRP) products used in urogynaecological disorders including vaginal atrophy, pelvic organ prolapse (POP), urinary incontinence, vaginal fistulas and vaginal mesh exposure. Methods: A meticulous search of the currently available literature on the use of PRP for the management of PFDs was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The vaginal health index (VHI) was significantly increased 6 months post treatment ( P < 0.0001 ) [23]. Similar outcomes were also observed in female sexual distress while patients were satisfied with the posttreatment outcome [4 ▪▪ ,23].…”
Section: Historical Data and Current Landscapementioning
confidence: 56%
See 4 more Smart Citations
“…The vaginal health index (VHI) was significantly increased 6 months post treatment ( P < 0.0001 ) [23]. Similar outcomes were also observed in female sexual distress while patients were satisfied with the posttreatment outcome [4 ▪▪ ,23].…”
Section: Historical Data and Current Landscapementioning
confidence: 56%
“…In the field of mesh surgery, preliminary in vitro and animal studies have also shown encouraging outcomes in improving the postoperative outcomes after the use of meshes coated with PRP [4 ▪▪ ]. The randomized experimental study by Dias et al evaluated the impact of PRP-coated polypropylene meshes compared to noncoated ones implanted in rabbit's vaginal submucosa [22 ▪ ].…”
Section: Historical Data and Current Landscapementioning
confidence: 99%
See 3 more Smart Citations